2010
DOI: 10.1002/cite.201000098
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐down of the Jet Zone Loop Reactor: Development of a Screening Tool for Chemical Reactions

Abstract: Scale-down of the Jet Zone Loop Reactor: Development of a Screening Tool for Chemical ReactionsThe jet zone loop reactor (JZR) is a high performance loop reactor in which it was shown on different reactions that the use of multiscale transport phenomena leads to a significant increase in the space-time yield and selectivity. As the use of a JZR in a semi-industrial scale means a high effort, the development of a comparable screening tool in a laboratory scale is the logical step in which the new technology can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…In these cases, it can be an adequate solution to provide even larger specific interfaces and enhance the mass transfer performance that way. Loop reactors and their derivatives have been proven to be excellent devices for this purpose [1][2][3][4]. As such, a jet loop reactor (JLR) is chosen as the tool for the desired process intensification.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, it can be an adequate solution to provide even larger specific interfaces and enhance the mass transfer performance that way. Loop reactors and their derivatives have been proven to be excellent devices for this purpose [1][2][3][4]. As such, a jet loop reactor (JLR) is chosen as the tool for the desired process intensification.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported in the last years that for large‐scale bulk chemical production a relationship between product quality and local mass transfer processes is present. However, these relationships could not be sufficiently explained or described until today . Examples for such reactions are the cumene oxidation, toluene oxidation (Scheme ) and also chlorination reactions …”
Section: Introductionmentioning
confidence: 99%
“…The achievable space time yields of biochemical reactions are determined by both, local mass transfer effects and the overall mass transfer capacity of the reactor . If high local reaction rates are achieved an efficient homogenization is required, otherwise oxygen and substrate gradients are formed and the aspired selectivity cannot be met . Already a few seconds of oxygen limitation can induce genes for a metabolic shift towards the production of anaerobic byproducts .…”
Section: Introductionmentioning
confidence: 99%
“…For JLRs, the efficient mass transfer performance relies on high local power inputs within the nozzle and subsequently the generation of a fine primary gas liquid dispersion . In case of the STR, mixing and the secondary dispersion of the gas phase is taking place at multiple stirrer blades and at the installed baffles.…”
Section: Introductionmentioning
confidence: 99%